Analysis of the airtightness measurement in single or double apartment house - Rokas Klabis (Vilnius Gediminas Technical University, 2021)
The mandatory energy performance certification of new buildings or buildings for sale has been introduced in all Member States in order to achieve European Union’s energy efficiency goals. The certification of buildings sets mandatory requirements for higher energy efficiency buildings’ level of airtightness. However, a bigger problem lies in existing older residential buildings, which are energy inefficient and do not require certification. The unused potential for energy savings observed here is related to the airtightness of single and double apartment residential buildings and energy efficiency related to airtightness of them. Therefore, this work analyses the airtightness of energy class D and lower buildings based on actual airtightness measurements and evaluates the possible energy saving potential associated with the application of airtightness measures based on the example of one inefficient single apartment building. The results show that increase of the airtightness in such buildings to 3 h–1 enables to reduce the energy costs related to the airtightness in Lithuania over a period of 10 years by 0.17 TWh per year.